2017
DOI: 10.4314/ijs.v19i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of gastrointestinal tract parasites of poultry and their environmental risk factors in poultry in Iwo, Osun State Nigeria

Abstract: This study was carried out to identify and estimate the prevalence of intestinal parasites of poultry in Iwo local council of Osun state, Nigeria. A total of 250 layers comprising of 75 chicks, 100 growers and 75 adults were examined from five different poultry houses between April and July 2016 in different areas during the survey. Our finding showed that 62% were infected with different species of parasites. Parasites identified includes Ascaridia galli; coccidian; Heterakis gallinae (C ecal worm); Syngamus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(8 reference statements)
3
4
2
Order By: Relevance
“…The predominance of coccidial infection followed by A . galli infection in the present findings was similar to earlier reports, from India [ 17 ], Cameroon [ 18 ], South Gujarat, India [ 9 ], and Nigeria [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predominance of coccidial infection followed by A . galli infection in the present findings was similar to earlier reports, from India [ 17 ], Cameroon [ 18 ], South Gujarat, India [ 9 ], and Nigeria [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…The published reports on prevalence of GIT parasites of poultry with associated risk factors from different parts of the world showed great variation (16-80%) [13][14][15][16]. The predominance of coccidial infection followed by A. galli infection in the present findings was similar to earlier reports, from India [17], Cameroon [18], South Gujarat, India [9], and Nigeria [19][20][21].…”
Section: Discussionsupporting
confidence: 87%
“…Surveys conducted in Ogun State [16; 17], Ondo State [18], Abuja (FCT) [19; 20], and in Borno State [21] however revealed lower prevalence of 6.8%, 4%, 7.7%, 14.6%, 25% and 12.6% respectively. Higher prevalence than what was recorded in this study were also reported among chickens in other parts of Nigeria [22;23;24]. These variations can be attributed to the different seasons in which these studies were conducted, the breed of chickens sampled, the farming systems and chicken management practices adopted in the respective study areas.…”
Section: Discussioncontrasting
confidence: 43%
“…The farm location influencing the presence of parasites reveals that there might be different management practices or parasite biodiversity in the area. However, farm location may not be a significant factor if the characteristics of the farms are similar [25]. On the other hand, the number of years the farm is in business was found to be another significant factor.…”
Section: Resultsmentioning
confidence: 99%